Kinetic effects of pressure on decomposition of solids - Vyazovkin, Sergey (International reviews in physical chemistry, 2020)
The kinetics of thermal decomposition of solids is discussed in connection with three major approaches to inducing pressure: by manipulating pressure of the product gas, by changing pressure of an inert gas, and by applying a mechanical force. The first two approaches are implemented in differential scanning calorimetry (DSC) and thermogravimetry (TGA), whose upper pressure limit is in the MPa range. The third approach is implemented in diamond anvil cells that extend measurements to the GPa range. In the GPa range a response of the rate to pressure is determined by the sign of the activation volume change. In the MPa range this response is determined by pressure of the gaseous product in the reaction zone. Manipulating the product gas pressure affects directly the kinetics of reversible decompositions as described by a number of models. Changing pressure of an inert gas results in indirect manipulation of pressure of the gaseous products that can engage in reaction with the reactant or another product and thus affect the kinetics of autocatalytic and reversible decompositions. These and other effects are discussed with the emphasis on changes in the activation energy and preexponential factor as a function of pressure, temperature, and conversion.